Association analysis of polymorphisms in SLK, ARHGEF9, WWC2, GAB3, and FSHR genes with reproductive traits in different sheep breeds - Tao, Meini; Li, Zhiqiang; Liu, Meng; Ma, Haiyu; Liu, Wujun (Frontiers in Genetics, 2024)
The aim was to investigate the relationship between polymorphisms of gene mutation loci and reproductive traits in local sheep breeds (Duolang Sheep) and introduced sheep breeds (Suffolk, Hu Sheep) in Xinjiang to provide new molecular markers for the selection and breeding of high fecundity sheep. The expression pattern of typing successful genes in sheep tissues was investigated by qPCR technology, providing primary data for subsequent verification of gene function. The 26 mutation loci of WWC2, ARHGEF9, SLK, GAB3, and FSHR genes were typed using KASP.Association analyses were performed using SPSS 25.0, and the typing results showed that five genes with six loci, WWC2 (g.14962207 C>T), ARHGEF9 (g.48271079 C>A), SLK (g.27107842 T>C, g.27108855 G>A), GAB3 (g.86134602 G>A), and FSHR (g.80789180 T>G) were successfully typed. The results of the association analyses showed that WWC2 (g.14962207 C>T), SLK (g.27108855 G>A), ARHGEF9 (g.48271079 C>A), and FSHR (g.80789180 T>G) caused significant or extremely significant effects on the litter size in Duolang, Suffolk and Hu Sheep populations.The expression distribution pattern of the five genes in 12 sheep reproduction-related tissues was examined by qPCR. The results showed that the expression of the SLK gene in the uterus, the FSHR gene in the ovary, and the ARHGEF9 gene in hypothalamic-pituitary-gonadal axis-related tissues were significantly higher than in the tissues of other parts of the sheep. WWC2 and GAB3 genes were highly expressed both in reproductive organs and visceral tissues. In summary, the WWC2 (g.14962207 C>T), SLK (g.27108855 G>A), ARHGEF9 (g.48271079 C>A), and FSHR (g.80789180 T>G) loci can be used as potential molecular markers for detecting differences in reproductive performance in sheep. Due to variations in typing results, the SLK (g.27107842 T>C) and GAB3 (g.86134602 G>A) loci need further validation.